THE POWER OF WORDS IN AN EMERGENCY: THE IMPORTANCE OF SPEECH IN AIRPORT FIRE SAFETY (Web of Technology: Multidimensional Research Journal, 2024)
This article explores the critical role of clear and effective communication during emergencies in airport fire safety scenarios. Airports are high-risk environments requiring swift, coordinated responses to ensure the safety of passengers, staff, and infrastructure. The power of words—spoken commands, alerts, and instructions—can significantly influence the outcome of emergency situations. This study highlights the importance of precise language, tone, and delivery to mitigate panic, facilitate evacuation, and enable collaboration among emergency response teams. Case studies and best practices are discussed to underscore how well-crafted verbal communication strategies can save lives and reduce damage during airport fire emergencies.